The Mw = 6.0, 7 September 1999 Athens Earthquake - Papadimitriou, P.; Voulgaris, N.; Kassaras, I.; Kaviris, G.; Delibasis, N.; Makropoulos, K. (2002)
On 7 September 1999 at 11:56 GMT a destructive earthquake (Mw = 6.0) occurred close to Athens (Greece). The rupture process is examined using data from the Cornet local permanent network, as well as teleseismic recordings. Data recorded by a temporary seismological network were analyzed to study the aftershock sequence. The mainshock was relocated at 38.105°N, 23.565°E, about 20 km northwest of Athens. Four foreshocks were also relocated close to the mainshock. The modeling of teleseismic P and SH waves provides a well-constrained focal mechanism of the mainshock (strike = 105°, dip = 55° and rake = -80°) at a depth of 8 km and a seismic moment M0 = 1.01025 dyn·cm. The obtained fault plane solution represents normal faulting indicating an almost north-south extension. More than 3500 aftershocks were located, 1813 of which present RMS < 0.1 s and ERH, ERZ < 1.0 km. Two main clusters were distinguished, while the depth distribution is concentrated between 2 and 11 km. Over 1000 fault plane solutions of aftershocks were constrained, the majority of which also correspond to N–S extension. No surface breaks were observed but the fault plane solution of the mainshock is in agreement with the tectonics of the area and with the focal mechanisms obtained by aftershocks. The hypocenter of the mainshock is located on the deep western edge of the fault plane. The relocated epicenter coincides with the fringe that represents the highest deformation observed on the differential interferometric image. The calculated source duration is 5 sec, while the estimated dimensions of the fault are 15 km length and 10 km width. The source process is characterized by unilateral eastward rupture propagation, towards the city of Athens. An evident stop phase observed in the recordings of the Cornet local stations is interpreted as a barrier caused by the Aegaleo Mountain.